The calcineurin regulator Sarah enables distinct forms of homeostatic plasticity at the Drosophila neuromuscular junction - Armstrong, Noah S.; Frank, C. Andrew (Frontiers in Synaptic Neuroscience, 2023)
The ability of synapses to maintain physiological levels of evoked neurotransmission is essential for neuronal stability. A variety of perturbations can disrupt neurotransmission, but synapses often compensate for disruptions and work to stabilize activity levels, using forms of homeostatic synaptic plasticity. Presynaptic homeostatic potentiation (PHP) is one such mechanism. PHP is expressed at the Drosophila melanogaster larval neuromuscular junction (NMJ) synapse, as well as other NMJs. In PHP, presynaptic neurotransmitter release increases to offset the effects of impairing muscle transmitter receptors. Prior Drosophila work has studied PHP using different ways to perturb muscle receptor function – either acutely (using pharmacology) or chronically (using genetics). Some of our prior data suggested that cytoplasmic calcium signaling was important for expression of PHP after genetic impairment of glutamate receptors. Here we followed up on that observation. We used a combination of transgenic Drosophila RNA interference and overexpression lines, along with NMJ electrophysiology, synapse imaging, and pharmacology to test if regulators of the calcium/calmodulin-dependent protein phosphatase calcineurin are necessary for the normal expression of PHP. We found that either pre- or postsynaptic dysregulation of a Drosophila gene regulating calcineurin, sarah (sra), blocks PHP. Tissue-specific manipulations showed that either increases or decreases in sra expression are detrimental to PHP. Additionally, pharmacologically and genetically induced forms of expression of PHP are functionally separable depending entirely upon which sra genetic manipulation is used. Surprisingly, dual-tissue pre- and postsynaptic sra knockdown or overexpression can ameliorate PHP blocks revealed in single-tissue experiments. Pharmacological and genetic inhibition of calcineurin corroborated this latter finding. Our results suggest tight calcineurin regulation is needed across multiple tissue types to stabilize peripheral synaptic outputs.